Bio-compatible piezoelectric material based wearable pressure sensor for smart textiles. (1st December 2022) - J, Abanah Shirley; S, Esther Florence; B S, Sreeja; Sankararajan, Radha
Abstract: With the rapid advancement of flexible wearable technology, bio-compatible textile piezoelectric pressure sensors are a promising candidates for next-generation sensing platforms to monitor human health. Smart textiles can be easily incorporated into our daily wear clothing in a breathable and conformable manner. In this study, a novel structural hierarchy consisting of a piezoelectric composite film Glycine–Chitosan (GC) sandwiched between two Zinc Oxide (ZnO) nanorods patterned conductive textile electrodes was developed. A low temperature hydrothermal method was used to grow ZnO nanorods directly on the conductive fabric, and a simple solvent casting technique was employed to form a GC film. Scanning electron microscopy and x-ray diffraction analyses were performed to investigate the growth of the bio-compatible piezoelectric materials. Under periodic deformation, the fabricated sensor exhibited a good piezoelectric response over a wide range of sensing pressures. The use of non-toxic, bio-compatible piezoelectric materials in the development of textile pressure sensors paves the way for the development of eco-friendly wearables.